The Effectiveness of Education Using Video Presentations on Improving Dental and Oral Health Knowledge in Grade IV Children in State Elementary Schools Bengalon 1 - Rengganis Gelistianti Rejeki; Ana Riolina; Dwi Kurniawati; Morita Sari (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: Dental and oral health problems in school-age children are still common and one of them is due to a lack of knowledge about how to maintain dental and oral health properly. Educational media in the form of video presentations can be used to improve student understanding because it combines visual and audio elements that are more interesting to children. This study aims to determine the effectiveness of dental and oral health education using presentation video media on the level of knowledge of grade IV elementary school students. Method: This study uses a quantitative approach with a quasi-experimental pretest–posttest design. The research participants amounted to 52 grade IV students of SD Negeri Bengalon 1 who were selected using the purposive sampling technique. Data collection was carried out using a dental and oral health knowledge questionnaire of 10 questions given before and after the intervention. The intervention was in the form of a 5-minute educational video on how to maintain healthy teeth and mouth, tooth brushing techniques, healthy food, and prevention of dental diseases. Data analysis was carried out using the Shapiro–Wilk normality test and the Wilcoxon Signed Rank Test. Result: The results showed an increase in students' knowledge scores after being given the intervention. The results of the Wilcoxon Signed Rank Test showed that there was a significant difference between the pretest and posttest scores with a significance value of 0.001 (p < 0.05). A total of 43 students experienced an increase in scores after being given education Conclusion: Dental and oral health education using presentation video media is effective in improving the knowledge of grade IV elementary school students. Video media can be used as an interesting and effective health learning method for school-age children.